STUDY CLUB: EFFORTS TO IMPROVE STUDENTS' ABILITY TO READ THE YELLOW BOOK - Reval Mhaulana Aminullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses efforts to improve students' ability to read books through the Study Club program. This research uses a descriptive qualitative approach. The results of this research show that Study Club activities can improve students' ability to read the Kitab Kuning.